Evaluation Effect of Amikacin-Cefepime Combination Against Biofilm Formation In XDR-Pseudomonas.aeruginosa - Mousa, Kawther Abd-Aladil; Ibraheem, Ahmed Harbi (Medical Science Journal for Advance Research, 2024)
Background: The intent of the research was to evaluate how the combination of amikacin and cefepim affected biofilm formation in ten clinical isolates of extensive druge resist pseudomonas aeruginosa A total of 295 clinical samples were obtained from patients suffering from burns, UTI , wounds, and CSF. Laboratory diagnosis is based on biochemical and morphological testing, and the VITEK-2 Compact system is used for confirmation. 53 Pseudomonas aeruginosa isolates from 295 samples were identified in the findings, representing 18% of the total samples . Susceptibility test showed that isolates had greater percentages of resistance to ceftazidime (72%)followed by cefepime (60%) , while has low resist to colstin (2%) . 35 isolates (66%) of Pseudomonas aeruginosa were detected as multi druge resist , ten (19%) bacterial isolates resist more than five classes of antibiotics which considered As extensive druge resistance (XDR) . All XDR pseudomonas .aeruginosa showing strong biofilm formation .Combinations of cefepime and amikacin are more effective than their individual at preventing P. aeruginosa from forming biofilms in an in vitro environment .